Grouping information for judgments - Shah, Anuj K; Oppenheimer, Daniel M (Journal of experimental psychology. General, 2011)
Models of cue weighting in judgment have typically focused on how decision-makers weight cues individually. Here, the authors propose that people might recognize and weight groups of cues. They examine how judgments change when decision-makers focus on cues individually or as parts of groups. Several experiments demonstrate that people can spontaneously pack information into cue groups. Moreover, group-level weighting depends on how people assess similarity or how they think of categorical hierarchies.